Marine and coastal ecosystems and climate change : a public awareness survey - Fonseca, Catarina (2022)
Hundreds of millions of people worldwide directly rely on marine and coastal ecosystems for their food, livelihoods and ways of life, yet these ecosystems are subject to a variety of pressures (UNEP, 2006; Hoegh-Guldberg et al., 2015; Korpinen et al., 2019). These pressures include climate change - one of the most urgent challenges societies are currently facing, with “long-lasting or irreversible” adverse consequences predicted as a result (IPCC 2018). Healthy marine and coastal ecosystems are a pre-requisite for the continuing delivery of ecosystem services, such as the provision of food, climate regulation and carbon storage. Therefore, it is critical to achieve a more sustainable management and effective protection of such valuable ecosystems. Policy makers are increasingly aware of the adverse effects of climate change and environmental degradation on our coasts and oceans. As public opinion influence decision-making on the actions to take and contribute to the success of their implementation (Rasmussen et al., 2017), it is important to understand how well informed the public is about climate change impacts and solutions in marine and coastal systems. In recent years, significant efforts have been made by the scientific community to raise public awareness of climate change and the links between healthy marine and coastal ecosystems and ecosystem service provision, including their role in mitigating and adapting to climate change (Barracosa et al., 2019). However, there has been little consideration of how the public perceives the interlinkages between climate change and its effects on marine and coastal ecosystems. Instead, most efforts have addressed climate change perceptions (van Valkengoed et al., 2022) Mildenberger et al., 2019) and marine threats perceptions (Ankamah-Yeboah et al., 2020; Lotze et al., 2018), separately. In the scope of the research project on “Marine Coastal ecosystems Biodiversity and Services in a changing world” (MaCoBioS) funded by the European Commission, people’s views on climate change, the value of marine and coastal ecosystems and the threats facing they face, as well as potential management options were investigated.